Molecular characterization and identification of SNPs in ATP1A1 isoform of sodium-phosphate adenosine triphosphatase across diverse breeds of riverine buffaloes (Bubalus bubalis) and Indian native cattle (Bos indicus): A plausible candidate gene for heat tolerance - KAUR, RAMNEEK; SODHI, MONIKA; SHARMA, ANKITA; SHARMA, VIJAY LAKSHMI; VERMA, PREETI; SWAMI, SHELESH KUMAR; KATARIA, RANJIT S; SINGH, MANOJ K; K, PARVESH; MUKESH, MANISHI (The Indian Journal of Animal Sciences, 2021)
In the present study, efforts were made to sequence characterize the selected exonic region (18–21) of ATP1A1 gene to identify variations/SNPs in different breeds of Indian riverine buffaloes and native cattle. The sequence characterization of selected intronic/exonic region (17–21) of ATP1A1 gene was carried out in a total of 120 samples which included 6 animals each of 8 buffalo breeds and 72 animals of 12 cattle breeds. Genomic DNA was extracted from the whole blood by enzymatic digestion using proteinase K using phenol:chloroform method.. Three sets of primers were designed using Primer3 software to amplify genomic region from intron 17 to intron 21 of ATP1A1 gene in both cattle and buffaloes. The amplified products were purified by enzymatic method and purified PCR products were sequenced using forward primers in an ABI 3100 Automated DNA Sequencer. The chromatogram of each sequence obtained was checked manually. Base calling was performed with Phred and contig assembly was done via Phrap/Cross_match/Swat tool available in the suite Codon code Aligner v. 3.5.1. The results revealed a total of 26 variations in exons 18–21 of ATP1A1 gene in riverine buffalo. Out of 26 variations, 6 (T27006876C, C27006599T, T27006345C, T27006330C, G27006309T and T27006240C) were distributed across 4 exonic regions and the remaining 20 were located in intronic region whereas in native cattle, only 2 SNPs were identified in exonic regions (18–21). SNP T27007767C was found to be a novel one in 18 intronic region of ATP1A1 gene in Indian cattle breeds. All 7 variations found in exonic region of both buffalo and cattle breeds were synonymous with the predicted changes in amino acids. The variations identified in ATP1A1 gene in the present study could be evaluated in future for their roles in heat tolerance trait in riverine buffaloes and native cattle.